Analysis of disaster preparedness knowledge and skills for teachers of SMA Negeri 1 Palas, South Lampung - Vina Sabella; Ratna Widiastuti; Muhammad Nurwahidin (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
This study aims to determine the level of disaster preparedness among the teachers of SMA Negeri 1 Palas in South Lampung. Palas is located near the Anak Krakatau. This area has high disaster risks, either from Anak Krakatau eruption, earthquake, or tsunami. That is why a study of disaster preparedness is needed. This research uses quantitative research methods. Data collection techniques used a Psychological First Aid questionnaire (PFA questionnaire). Psychological First Aid is widely used for psychosocial support in disaster preparedness. The research subjects were 30 teachers. The data analyzed with descriptive statistical analysis. Based on the results of the research, it shows that the teachers at SMA Negeri 1 Palas understand about giving Psychological First Aid as a disaster preparedness support quite well, showed with the frequency of high category of 47%, the frequency of moderate category of 50%, and the frequency of low category of 3%. Meanwhile, it showed that there were the teachers’ understandings about 1) providing direct care of the Psychological First Aids, with the frequency of high category of 80%, the frequency of moderate category of 20%, and the frequency of low category of 0%; 2) high-risk people identification of the Psychological First Aids, with the frequency of high category of 63%, the frequency of moderate category of 37%, and the frequency of low category of 0%; and 3) design follow up of the Psychological First Aids, with the frequency of high category of 73%, the frequency of moderate category of 20%, and the frequency of low category of 7%.